(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
Although linguists have noticed a decline in the use of idioms in creolophone speech during the last period (Mauriol, 2009), our data (twenty hours of recordings of non professional participants to the radio broadcasted programme Pawol tout Moun (« Everybody has his say », Martinique 1re), reveal that the use of metaphorical idioms remains an important device of communication for Martinican speakers. Recourse to metaphorical idioms in the corpus pursues several objectives, such asto stress the speaker’s point of view or to announce the argumentative structure and orientation of the speaker’s discourse. The interaction between specific idioms, different rhetoric devices and occasional defreezing of these idioms increases the communicative potential and the discourse-strategic function of these lexical units. In the critical and emotional genre typical of Pawol tout Moun, recourse to metaphorical idioms stands out as a major discourse strategy, which seems to pertain to a universe of discourse inherited from a civilization based on oral tradition (Bernabé, 1997).